SAMU (Simulation of Multi-Agents and Urban Modelisation): Contribution to the study of urban anthill - Banos A.; Godara A.; Lassarre S. (My University, 2025)
Developed in the context of artificial intelligence, agentbased simulation has been widely used in the context of traffic simulation. In spite of the fundamental role in the system of urban daily mobilities, walking remains a important mode of displacement well-known. But unfortunately, there are very rare works which have been done in this field, so from this point of view, a virtual urban environment or a simulation software. SAMU is created and is populated with autonomous agents like pedestrians and motorists of multi- agents type. Different constraints, affecting the mobility of the whole system are considered. The model belongs to the microscopic category, where pedestrians/vehicles behave in their environment by making a sequence of decisions. The interaction among vehicles and pedestrians is also incorporated which signifies the accident risk of pedestrians. Netlogo which is a multi agent based modeling language is used as the programming platform for SAMU. Copyright © IICAI 2005.